2006
DOI: 10.1243/095440506x77599
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Edge Quality Variation in Precision Machining of Single Crystal and Polycrystalline Materials

Abstract: The surface and edge quality of single crystal and polycrystalline copper workpieces has been observed to vary significantly as a function of crystallographic orientation. At the precision scale, the chip formation process is influenced by the microstructure of the material, such as grain boundaries and grain orientation in polycrystalline materials, and crystallographic orientation in single-crystal materials. Such variation in the microstructure has a significant effect on the resulting surface, edge, and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 12 publications
(13 reference statements)
0
16
0
Order By: Relevance
“…In general they confirmed that burr size is reduced and cutting ability increased as drill size decreases. Min et al [15] found that grain orientation affected burr formation in drilling of polycrystalline copper, Fig. 14. A single material may produce a ductile-like cutting mode in one grain and brittle-like cutting in another, indicating that favorable and non-favorable cutting orientations for good surface and edge condition exist as a function of crystallographic orientation.…”
Section: Burrs In Precision Machiningmentioning
confidence: 99%
See 2 more Smart Citations
“…In general they confirmed that burr size is reduced and cutting ability increased as drill size decreases. Min et al [15] found that grain orientation affected burr formation in drilling of polycrystalline copper, Fig. 14. A single material may produce a ductile-like cutting mode in one grain and brittle-like cutting in another, indicating that favorable and non-favorable cutting orientations for good surface and edge condition exist as a function of crystallographic orientation.…”
Section: Burrs In Precision Machiningmentioning
confidence: 99%
“…Min et al [15] conducted micro-fly cutting and microdrilling experiments on single crystal and polycrystalline OFHC copper in order to understand the effects of crystal orientation, cutting speed, and grain boundaries on surface roughness, chip formation, and burr formation. Certain crystallographic orientations were found to yield rougher surface finish, as well as significant burrs and breakout at the tool exit edge.…”
Section: Burrs In Precision Machiningmentioning
confidence: 99%
See 1 more Smart Citation
“…al. has demonstrated variation in surface finish and cutting force in continuous face turning of single crystal copper [3], and work done by the authors has demonstrated a significant change in chip morphology and surface/edge condition in microdrilling and ultraprecision flycutting [4], and in ultraprecision machining of single crystal copper [5]. Brinksmeier et.…”
Section: Introductionmentioning
confidence: 99%
“…To shorten polishing time, it is necessary to make a smoother surface at the ultra-precision cutting process stage [8][9][10][11]. In addition, the single-crystal CaF 2 's characteristics indicate hard brittleness and crystal anisotropy [12][13][14]. Yan [15] showed that crack initiation depended on cutting direction and that the http://dx.doi.org/10.1016/j.precisioneng.2014.11.007 0141-6359/© 2014 Elsevier Inc. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%